2013
DOI: 10.1155/2013/875958
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Dengue Virus Binding Proteins inAedes aegyptiMosquitoes andAedes albopictusCells

Abstract: The main vector of dengue in America is the mosquito Aedes aegypti, which is infected by dengue virus (DENV) through receptors of midgut epithelial cells. The envelope protein (E) of dengue virus binds to receptors present on the host cells through its domain III that has been primarily recognized to bind cell receptors. In order to identify potential receptors, proteins from mosquito midgut tissue and C6/36 cells were purified by affinity using columns with the recombinant E protein domain III (rE-DIII) or DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…The enolase TIP identified in the present study was previously reported to be upregulated in L1 thrips infected with TSWV (18), and enolase was also upregulated in response to rice stripe virus (RSV) in bodies of the planthopper vector, L. striatellus (57). In the case of flaviviruses, Aedes aegypti enolase was shown to directly interact with purified virus and recombinant envelope glycoprotein of dengue virus (58) and West Nile virus envelope protein (59). The localization of this enolase in brush border membrane vesicles of this mosquito species (60) strengthens the case for a proposed receptor role in virus entry into vector mosquito midguts.…”
Section: Discussionsupporting
confidence: 58%
“…The enolase TIP identified in the present study was previously reported to be upregulated in L1 thrips infected with TSWV (18), and enolase was also upregulated in response to rice stripe virus (RSV) in bodies of the planthopper vector, L. striatellus (57). In the case of flaviviruses, Aedes aegypti enolase was shown to directly interact with purified virus and recombinant envelope glycoprotein of dengue virus (58) and West Nile virus envelope protein (59). The localization of this enolase in brush border membrane vesicles of this mosquito species (60) strengthens the case for a proposed receptor role in virus entry into vector mosquito midguts.…”
Section: Discussionsupporting
confidence: 58%
“…Laminin receptors, on the other hand, have also been implicated in DENV entry into cells of the mosquito vector Aedes albopictus (89). In the second DENV mosquito vector Aedes aegypti, E glycoprotein affinity enrichment and MS identified enolase, beta-adrenergic receptor kinase (beta-ARK), and cadherin as putative entry factors (90). Further postulated receptors for flaviviruses identified by virus overlay protein binding assay followed by MS identification, are the 78 kDa glucose-regulated protein, mosquito 45 kDa, and 64/67 kDa proteins for DENV (91)(92)(93)(94)(95) and alpha V beta 3 integrin, the C45 like phosphatase mosPTP-1 and C-type lectin mosGCTL-1 for WNV ( Fig.…”
Section: Zikvmentioning
confidence: 99%
“…The results for HspA5 protein (isoform of the Hsp70 chaperone) [15] corroborates data found during blood feeding in the A. aegypti midgut, where there is an increase in the gene expression of Hsp70 in response to stress [16]. However, little is known about the function of elongation factor 4 (EF4), but it is considered essential for protein synthesis and cell viability due to its homology to EF1 [17,18], which increases its expression in the A. aegypti midgut following infection with DENV-2, suggesting that it may assist in viral replication [6].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, when infected with CHIK virus or Dengue virus type 2 (DENV-2), modified expressions of proteins associated with regulatory, metabolic and structural pathways in the midgut were noted [5]. Moreover, midgut proteins linked to DENV-2 infection, including enolase, beta-ARK, and cadherin that can act as receptors, and the elongation factor EF-1 alpha/Tu that is important for viral replication [6], have recently been identified.…”
Section: Introductionmentioning
confidence: 99%